Particle exposure during the 2013 haze in Singapore : importance of the built environment - Zhou, Jin (2015)
The 2013 haze was the most serious air pollution event in Singapore's history. Individual exposures to particulate matter differ (a) according to time patterns of behaviour and (b) with the varying degrees of protection provided by buildings against penetration and persistence of outdoor particles. Utilizing real-time personal monitoring, we evaluated exposures to size-segregated fine particulate matter (PM) of five office workers for six days during the latter portion of the 2013 haze event. The outdoor volume concentrations of particulate matter (0.3–2.5 μm diameter) during moderate and light haze days were in the ranges 15–21 μm3/cm3 and 7–10 μm3/cm3, respectively. More than 80% of total daily exposures occurred indoors in workplaces and residences. The daily-integrated personal exposures for the five subjects during the moderate and light haze days were 140–454 (μm3/cm3)-h and 66–239 (μm3/cm3)-h, respectively. Exposure factors for the five participants, quantifying the extent of exposure reduction associated with being indoors, had daily average values ranging from 0.32 to 0.75. The results of this study contribute toward deeper understanding the degree of protection provided by the buildings from pollution of outdoor origin. The work also contributes knowledge regarding personal exposure to particulate matter during air pollution episodes, especially for tropical climates.